Pemanfaatan Software Akuntansi untuk Optimalisasi Efisiensi dan Akurasi Proses Keuangan dalam Organisasi - Wahyuni, Lidia; Sofilda, Eleonora; Hamzah, Muhammad Zilal (Dirkantara Indonesia, 2025)
This community service project aims to enhance the competence of vocational school teachers in West Jakarta in using accounting software to improve the quality, efficiency, and accuracy of education. This activity is driven by the urgent need to upgrade teachers' skills before the competency test conducted by the Professional Certification Institute (LSP), using the latest technology. The implementation of this community service employs a descriptive qualitative approach through training, mentoring, and evaluation. The training utilizes Accurate online accounting software, chosen for its capability to meet the financial reporting standards required by schools. The results of the training showed a significant improvement in participants' skills, as evidenced by the comparison of pre-test and post-test results. The participants also reported increased confidence and readiness to face the Accounting Technician competency test. To ensure the sustainability of the program, periodic mentoring is planned, and the scope of the training will be expanded to involve more vocational school teachers in the area. This improvement in competence is expected to contribute to better financial management in schools and ultimately enhance the quality of education at the vocational high school level.